Pengaruh Motivasi dan Pelatihan Kerja Terhadap Kinerja Karyawan pada PT OSI Electronics Indonesia Batam - Rina Desika Nainggolan; Hikmah Hikmah (Komunitas Dosen Indonesia, 2022)
Human undoubtly still one of the most important source that company should be aware of, therefore to find out what things that impactful on performance is a must. The method used were using test of validity, reliable test, normal test, multicolinearity test, heterocedasticity test, multiple liniar regresion analytict, coeficient of determination analytic, t test and F test by using the help of software SPSS 26 . Data collected by using the answer of questioner that spread to to 150 respondant. This test obtained a calculated f value of 31.558, with table F the magnitude is 3.06. In this test, the relationship of all variables which are motivation and job training are both giving impact. This statement is supported by the calculated F which is higher than the F table, and the significant value is 0.000 which is fewer than 0.05. and it come to a conlusion that motivation and job training affect work performance of OSI Electronics employees